Development of the novel Pictor PictVet™ Mycoplasma bovis IgG multiplex ELISA for the detection of Mycoplasma bovis infections in cattle - Furuya, Yoichi; Bugde, Piyush; Shetty, Bhoopika; Hashimi, Farina Nor; Gholizadeh, Hamideh; Whittaker, Dave; Tejerina, Jimena; Gordon, Natasha; Tivendale, Kelly A.; Wawegama, Nadeeka K.; Browning, Glenn F.; Kinga, Andrea (Frontiers in Veterinary Science, 2025)
Early and accurate detection of infection with Mycoplasma bovis (M. bovis) is critical for managing disease caused by this pathogen, particularly in eradication campaigns, such as New Zealand’s National M. bovis Eradication Programme. In response to the launch of the eradication programme, we developed and evaluated a novel multiplex ELISA assay—the Pictor PictVet™ M. bovis IgG Multiplex ELISA. Two M. bovis antigens, MilA and K310, were incorporated into the Pictor PictVet™ M. bovis Multiplex ELISA to detect M. bovis-specific serum IgG. Studies were conducted to determine the assay agreement with the ID Screen® Mycoplasma bovis Indirect ELISA (IDvet). A collection of sera from New Zealand cattle, previously characterized as IDvet-positive (+) and IDvet-negative (−), was used for these evaluations. Binding to the two different M. bovis antigens, MilA and K310, had high estimates of agreement, with PPAs of 89.3 and 96.4%, and a NPA of 99.2%. When the results from both the MilA and K310 components of the assay were combined to determine the assay outcome, the PPA increased to 100%, while the NPA remained high, at 98.4%, with an overall agreement of 98.9%. Multiplexing of two M. bovis antigens enhanced the diagnostic performance of the indirect ELISA in detecting M. bovis-specific IgG in serum samples. These findings suggest that the Pictor PictVet™ M. bovis IgG Multiplex ELISA could be a valuable tool for early detection and surveillance for infection with M. bovis in cattle.